Not only Modern Technology but also the COVID-19 Pandemic has led to Cashless Economy in India: An empirical investigation (International Journal of Food and Nutritional Sciences, 2022)
In this changing age, rapid technological growth has led us into the digital world. With this digital world due to the continuing level of technological infrastructure and policy changes, there has been an increase in the number of payment methods. In this growing age, it is necessary to keep up with the latest technology, one of which is to change the way we make and receive payments. The Cashless Economy seems to be similar to Canada and Sweden as evidenced by studying Forex Cashless Economy is based on purchases made by credit cards, debit cards, wallets or digital means. An economy without money is less expensive, it grows, it interacts with businesses, it involves people financially, etc. You have different challenges that people can no longer run away from, poor trade security, inadequate infrastructure etc. It is beneficial for industries like UBER and OLA. The pros and cons of a cashless economy will help us determine whether the world should run a cashless economy or not? Covid-19 has had a profound impact on the economy, and how it became a pillar of a moneymaking economy will help us better understand the concept of a money-making economy. The cash- strapped economic system at this time has its own important significance. The list of questions and ideas presented in this report will help us to understand people's perceptions of a financially viable economic system. This research contain survey which include people from all professions that are students, people doing service, people who are self-employed, people doing business, it included housewives too. It included qualified people who did SSC, HSC, UG, PG, DOCTRATE and many other degrees. Hence all age categories with all types of qualifications and professions were asked. Additional analysis will be performed on the primary as well as secondary data.